Enhancing adaptive capacity and improving water security through water storage in South Asia - International Water Management Institute (International Water Management Institute, 2022)
Natural and built stores of freshwater are critical for both ecosystem vitality and societal development, enabling natural and human systems to cope with temporal variations in water supply and demand. For societies, the importance of water storage has grown as human population has increased and socioeconomic development has advanced. The significance of water storage will continue to grow as the impacts of climate change become more pronounced.